The Chemical Composition and Physical Properties of the Light and Heavy Tar Resulted from Coconut Shell Pyrolysis - Uswatun Hasanah; Bambang Setiaji; Triyono Triyono; Chairil Anwar (Chemistry Department, The University of Brawijaya, 2012)
The tar resulted from pyrolysis of coconut shell is a waste. It is important to be clarified their chemical composition and physical properties in order to find out their feasibility as source of a fuel. This research was resulted two immiscible organic fractions, and these were further determined their physical properties such as water composition by using ASTM D-95 methods, ash composition (ASTM D-482), flash point C.O.C (ASTM D-92), kinematics of viscosity (ASTM D-445), and caloric valued using bomb calorimetric. In addition, tar composition was determined by gas chromatography-mass spectrometry (GCMS). The result provided oil which was categorized as light and heavy bio-oils. The light bio-oil has specific gravity 0.99, ash content 0.01%, kinematics viscosity 25.5 cSt, flash point <27 oC, pH 3 and heating value 10304 kcal/kg. On the other hand, heavy bio- oils gave specific gravity 1.13, ash 0.46%, kinematics viscosity 185 cSt, flash point 134 oC, pH 2.5 and heating value 6210 kcal/kg. Moreover, the light bio-oil contained 79 compounds which was composed of phenol 16.4%, hydrocarbon 12.4%, phenolic 27.6%, other oxygenated compounds 53.6%, and acetic acid 3%, meanwhile the heavy bio-oils contained of 18 compounds which was consisted of phenol 31.2%, lauric acid 6.0%, phenolic 27.6%, and other oxygenated compounds 35.3%, respectively. With this result, it was clarify that these bio-oils could not be used directly as a fuel for motor nor diesel machinery.